The identifying of deaf-blind communication forms for the planning of therapeutic interventions - Martins, Emerson Fachin; Ivanov, Nadia (Acta Fisiátrica, 2009)
Visual and auditory disorders can affect motor and cognitive developments in children and compromise the functional acquisition in adults. Sensory impairments can alter the quality of the perception presented to the brain influencing the learning. In such cases the sensory adaptation is a necessary condition for the supplying of information that will benefit the development of the deaf-blind. Through the present study the communication forms presented by deaf-blind children and adults were verified aiming to identify strategies for the planning of therapeutic interventions. In order to accomplish that 19 families (with one of the members being deaf-blind) were interviewed. The deaf-blind subjects were divided into two groups according to their age, being considered as children subjects up to 17 years old and adults subjects more than 17 years old. The results didn’t show any predominant expressive communication form between the two age groups. However LIBRAS (brazilian sign language) was significantly more used by the adults in receptive communication forms than the other categories. It was concluded that professionals attending deaf-blind subjects must learn other forms of communication (mainly LIBRAS) to interact with deaf-blind patients and to plan therapeutic interventions appropriately.